FUNGSI KEPALA SEKOLAH DALAM MEMBINA KOMPETENSI PEDAGOGIK GURU - Pujianto Pujianto (Manajer Pendididikan, 2015)
This study aims in general to find out the principal functions in promoting pedagogical competence of teachers at SMK Negeri 2 Lubuklinggau. The method used is descriptive qualitative . The subjects were principals, vice principals and teachers. The technique used for collecting data are interview, observation and documentation. The general conclusion of this research is the principal function in the formation of pedagogical competence of teachers are being implemented effectively either of the function conceptually, technically and function.Keyword: principal, teachers, pedagogical competence